Design and fabrication of E-band silica based dense wavelength-division multiplexing (DWDM) AWG - Feng Han; Jiashun Zhang; Liangliang Wang; Pengwei Cui; Yue Wang; Junming An; Jun Chen; Bingli Sun; Tianhong Zhou (Results in Optics)
A E-Band,48 channels flat top silica based dense wavelength-division multiplexing (DWDM) arrayed waveguide grating (AWG) was designed and fabricated with 0.75 % relative refractive index difference. In order to reduce the center wavelength drift caused by the refractive index of silica material changing with external environmental temperature, the AWG chip was athermal packaged, and the center wavelength drift was reduced from 8.2 pm/° C to 0.643 pm/° C. The transmission spectra were measured, which the results shows that optical performance is uniform. The tested 53.12 GBPS pam-4 high-speed transmission eye signals are clearly visible, extinction ratio is more than 2.7 DB. The high-performance AWG provides an application basis for e-band data center transmission.